Designs on the desert: camouflage, deception and the militarization of space. (April 2014) - Forsyth, Isla
Throughout the Second World War camouflage was employed to conceal and counterfeit the military's presence in diverse landscape habitats; a technology designed to wipe out revealing patterns and inscribe false forms, all in order to make of enemy reconnaissance a glass eye. It was on the plains of the North African desert that the technology proved its effectiveness for military strategy. The desert was an expansive, shifting environment, demanding a new relationship between modern militarism and knowledge of the earth's surface. Where aerial reconnaissance could threaten to expose military desert designs, other forms of visual literacy were developed to engage with the vertical, as well as the horizontal, plane, all in order to camouflage military movements. This paper critically considers the triangulation of the technology of the aeroplane, and the camera, alongside the granular surface of sand. It explores the working practices of British desert camoufleurs, a diverse group of practitioners, including artists, scientists, filmmakers and, less expectedly, a magician, who were handpicked by the military due to their skills in visual literacy. Their innovations in camouflage form a narrative focusing on the development of desert-based design practices that subsequently arose from military engagements with this environment. The paper seeks to show both the aesthetic and the political implications of these military incursions into the desert, telling how the militarization of the desert exploited a land of mirages to deadly effect.